Peranan Humas Dalam Meningkatkan Kesadaran dan Partisipasi Masyarakat pada Kegiatan di Desa Mojosari Kecamatan Puger - Djoko Supriatno; Ahmad Nur Holis; Moh. Wildan Faizul Asnan; Yovial Arif Hariyadi; Santo Hadi Wijaya; Fahri Aula AlfaIdzi; Moh. Qurtubi (Al-Khidmah Jurnal Pengabdian Masyarakat, 2022)
Real work lectures (KKN) are a form of curricular partner which is an implementation of the Tri Dharma of higher education to provide work experience and student learning in community empowerment. Real work lecture activities are a golden opportunity for students to find the right solutions and strategies in dealing with problems that exist in the village. The placement of KKN student locations is mostly directed at villages that have superior potential but still lack community skills in managing. The purpose of this study was to determine the role of real work lectures as part of increasing public awareness and participation in an activity. The sample in this study is the community in the location around KKN. This research method is Field Research with data collection through interviews, observation, and documentation. From the results of research that has been obtained that the role of Community Service Program in increasing Public Awareness and Participation in an Activity is highly appreciated by the Community Around KKN.